Kecanggihan Teknologi Informasi, Partisipasi Manajemen, Kemampuan Teknik Personal, dan Efektivitas Sistem Informasi Akuntansi - Putri, Tya Adiantari; Juliarsa, Gede (E-Jurnal Akuntansi; Vol 33 No 11 (2023), 2023)
This research aims to determine the influence of information technology sophistication, management participation and personal technical abilities on the effectiveness of accounting information systems at LPDs in Denpasar City. The number of samples used was 29 LPD. Determination of the sample using purposive sampling technique. Data was collected using a questionnaire, then analyzed using multiple linear regression analysis. The research results show that the sophistication of information technology has a positive effect on the effectiveness of the accounting information system, management participation has no effect on the effectiveness of the accounting information system, personal technical abilities have a positive effect on the effectiveness of the accounting information system. Keywords: information technology sophistication; management participation; personal technical capability; accounting information system effectiveness